Faker - Korman, Gordon (New York : Scholastic Press, 2024)
Trey knows the drill: His dad gets him into a school full of kids with rich parents. Trey makes friends, and his dad makes connections. Soon, there's the con, where Trey's dad suckers the other parents into investing in one of his schemes. Once the money's in the bank, Trey, his sister, and their dad are on the run... until they set up somewhere else and start again. Trey believes his father when he says no one's getting hurt. After all, these parents have money to spare. But Trey's starting to get tired of running... and lying... and never having a friend for longer than a few months. But how do you get your family to stop lying when your lives depend on it?
Ages 8-12.
Grades 3-7.
Keywords: Families -- Juvenile fiction; Ethics -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Honesty -- Juvenile fiction; Swindlers and swindling -- Juvenile fiction; Truthfulness and falsehood -- Juvenile fiction; Friendship -- Juvenile fiction; Rich people -- Juvenile fiction; Family life -- Fiction; Fathers and sons -- Fiction; Swindlers and swindling -- Fiction; JUVENILE FICTION / Social Themes / Values & Virtues; JUVENILE FICTION / Family / Parents; Swindlers and swindling -- Juvenile fiction; Father-son relationship -- Juvenile fiction; Siblings -- Juvenile fiction; Honesty -- Juvenile fiction; Family life -- Juvenile fiction; Domestic fiction; Humorous fiction; Novels